Assessing students' perceptions of the effects of a new Canadian longitudinal pre-clerkship family medicine experience. Issue 3 (3rd May 2016) - Willoughby, Karen A.; Rodríguez, Charo; Boillat, Miriam; Dove, Marion; Nugus, Peter; Steinert, Yvonne; Lalla, Leonora
Abstract: Background : Despite the implementation of longitudinal community-based pre-clerkship courses in several Canadian medical schools, there is a paucity of data assessing students' views regarding their experiences. The present study sought to measure students' perceived effects of the new Longitudinal Family Medicine Experience (LFME) course at McGill University. Methods : A 34-item questionnaire called the 'LFME Survey (Student Version)' was created, and all first-year medical students completed it online. Results : The participation rate was 64% (N = 120). Eight factors were identified in the factor analysis performed: overall satisfaction, satisfaction with preceptor, knowledge, affective learning, clinical skills, teaching/feedback, professional identity/professionalism and attitude toward primary care. Factor composite scores were above 4.5/7, indicating that students had positive perceptions of the LFME. Students felt that the LFME was a valuable educational experience and that their preceptors were good role-models. The course improved students' confidence, reinforced their commitment to being a physician and increased their positive attitude toward primary care. Interpretation : Along with similar pre-clerkship courses, the LFME provides a valuable context for developing students' clinical skills, providing real-world cases, teaching patient-centred care and improving attitudes toward primary care. The LFME Survey appears to be a promising and innovative tool that deserves further validation.